Relationship between strategic human resource management and organizational performance: evidence from selected Malaysian firms - Che Rose, Raduan; Samy, Naresh Kumar; Ibrahim, Hazril Izwar (EuroJournals, 2008)
Based on the universal and contingency approach, the relationship between strategic human resource management (HRM) practices and organizational performance have been examined in the Malaysian electrical and electronic sector. The finding provides support for the universal perspective and the resource-based theory that a firm’s human capital pool that is embedded within a synergistic HRM practices will lead to a better organizational performance. It has also proven the idea propagated by institutional theorist that firms will adopt best practices to survive external pressures like economic uncertainty and the market environment.